Brain Circulation and its Role in Knowledge Diffusion and Economic Growth Lessons for Sri Lanka: A Systematic Literature Review - Caldera, R.; Amirthalingam, Kopalapillai (Department of Economics, University of Colombo, Sri Lanka., 2025)
While the migration of highly skilled workers and professionals from developing countries is traditionally viewed as detrimental to the source countries, the emerging concept of brain circulation presents a controversial view on the subject. This systematic literature review investigates the concept in depth for its implications on knowledge diffusion and economic growth in the context of developing countries, to draw implications on Sri Lanka, a country grappling with severe brain drain. The study follows the guidelines of PRISMA, analysing information from 63 studies conducted between 2000 and 2024 on developing countries. Through the analysis of existing literature, the study identifies key factors influencing brain circulation, including return migration, successful reintegration of returnees, and the importance of diasporic connections. It also explores mechanisms for knowledge transfer and technology diffusion that can stimulate economic growth in developing countries. Through the lens of theories on economic development, the implications will be analysed to derive the impacts on economic growth. The findings highlight the critical need for Sri Lanka to develop strategic policies that address barriers to reintegration, foster diaspora engagement, and implement structural reforms to harness the potential of brain circulation.
Keywords: Brain Gain; Brain Circulation; Knowledge Diffusion; Brain Drain; Return Migration